Sono-peroxi-coagulation (SPC) as an effective treatment for pulp and paper wastewater: Focus on pH effect, biodegradability, and toxicity - Eslami, Akbar; Kashani, Mohammad Reza Khavari; Khodadadi, Ahmad; Varank, Gamze; Kadier, Abudukeremu; Ma, Peng-Cheng; Madihi-Bidgoli, Soheila; Ghanbari, Farshid (ELSEVIER, 2021)
In a comparative approach toward treating real pulp and paper wastewater (PPWW), iron-based electro-chemical processes such as peroxi-coagulation (PC), electrocoagulation (EC), electro-Fenton (EF), and ultrasound-assisted PC, EC, and EF were investigated. Sono-peroxi-coagulation (SPC) process showed the best performance for treating the PPWW. The optimal results were achieved under reaction time 50 min, current density 140 mA, and pH = 2.0. Employing the SPC process for treating PPWW under optimal conditions, the best COD removal efficiency (81.7%) was achieved. Also, continuous pH adjustment of the solution, as compared to lack of adjustment, showed a significant influence on COD removal efficiency (more than 10%). The effect of pH on the SPC process and the kind of electro-chemical treatment process utilized, on biodegradability were investigated using BOD/COD ratio and average oxidation state (AOS). In comparison with other electro-chemical processes used in this study, the best biodegradability results were obtained for the SPC process in pH = 2, being 0.4 and 0.94 for BOD/COD ratio and AOS, respectively. SPC process compared to the sono EF process had superior COD removal efficiency and their difference in performance reached near 40%. The influence of sonication was obtained 11.3% and 9% for PC and EF processes respectively. In evaluating the toxicity, the best germination index of Raphanus sativus, irrigated by treated wastewater samples, was achieved 77.9% for the SPC process. The application of US for electrochemical process increased energy consumption and cost of process considerably. The sludge of SPC was also evaluated by Fourier transform infrared spectrum (FTIR), X-ray diffractometer (XRD) and field emission scanning electron microscope (FESEM).
Keywords: Biodegradability; Electro-Fenton; Peroxi-coagulation; Phytotoxicity; Pulp and paper wastewater; Ultrasound; ELECTROCHEMICAL DEGRADATION; AQUEOUS-MEDIUM; FELT CATHODE; ELECTROCOAGULATION; REMOVAL; OXIDATION; DECOLORIZATION; COLOR; ACID; Engineering; Water Resources